The National Preventive Mechanism is a legal institution for the protection of human rights in the Republic of Kazakhstan - Turlayev, A.V.; Sopykhanova, A.B. (Bulletin of the Karaganda University “Law Series”, 2025)
The article discusses the legal regulation issues in the National Preventive Mechanism in the Republic of Kazakhstan. The activities of the National Preventive Mechanism are considered a legal institution of great importance for torture prevention, as well as cruel treatment and punishment, conditioned by international standards implemented in national legislation. The research purpose is to analyze the legal institute’s “National Preventive Mechanism”, identifying legal regulation problems in its activities and developing ways to overcome them. The research is carried out through general scientific and special legal methods, using analysis and theoretical provisions and legal norms generalization and the implementation practice. Based on the comparative legal process, the main trends in developing the National Preventive Mechanism Institute are currently being identified. The analysis of the specifics of the National Preventive Mechanism in Kazakhstan and its consolidation in legal acts and international standards is carried out. Main result of the research is the provision on the need to improve legal measures aimed at harmonizing national legislation in the prevention of torture with international standards in this area. The conclusions suggest the development and improvement of legal norms that specify the procedure for conducting preventive visits by members of the National Preventive Mechanism, as well as the procedure for financing and ensuring the independence of the human rights institution activities.